Lipid coating technology: A potential solution to address the problem of sticky containers and vanishing drugs. Issue 3 (1st July 2021) - Ma, Gamaliel Junren; Yoon, Bo Kyeong; Sut, Tun Naw; Yoo, Ki Yeol; Lee, Seung Hwa; Jeon, Won‐Yong; Jackman, Joshua A.; Ariga, Katsuhiko; Cho, Nam‐Joon
Abstract: Pharmaceutical drugs and vaccines require the use of material containers for protection, storage, and transportation. Glass and plastic materials are widely used for packaging, and a longstanding challenge in the field is the nonspecific adsorption of pharmaceutical drugs to container walls – the so‐called "sticky containers, vanishing drugs" problem – that effectively reduces the active drug concentration and can cause drug denaturation. This challenge has been frequently discussed in the case of the anticancer drug, paclitaxel, and the ongoing coronavirus disease 2019 (COVID‐19) pandemic has brought renewed attention to this material science challenge in light of the need to scale up COVID‐19 vaccine production and to secure sufficient quantities of packaging containers. To reduce nonspecific adsorption on inner container walls, various strategies based on siliconization and thin polymer films have been explored, while it would be advantageous to develop mass‐manufacturable, natural material solutions, especially ones involving pharmaceutical grade excipients. Inspired by how lipid nanoparticles have revolutionized the vaccine field, in this perspective, we discuss the prospects for developing lipid bilayer coatings to prevent nonspecific adsorption of pharmaceutical drugs and vaccines and how recent advances in lipid bilayer coating fabrication technologies are poised to accelerate progress in the field. We critically discuss recent examples of how lipid bilayer coatings can prevent nonspecific sticking of proteins and vaccines to relevant material surfaces and examine future translational prospects. Abstract : Layman's summary: Vaccines and medical drugs can stick onto the surface of container walls, which is often referred to as the "sticky containers and vanishing drugs" problem. Lipid coating technology is a potential solution that can overcome this problem and improve pharmaceutical quality control.